(3GdbSe GdQGHY aj hVY GdBdGJ GdLjHjIs - (3CHh Ydj TQa GdOjf GdMSf Hf Ydj Hf YeQ GdeQGcTj,J (B660 (3g` s
(3ChdgG (B:s
(3GdbSe GdQGHY ai hVY GdBdGJ GdLjHjI hgj GdJi JDOi Edi GdeWdhH HGdJfGSH hjTJed Ydi CQHYI aUhd s
(3BNQgG (B:s
(3hCeG eG jQSe Ydi XgQ GdCSWQdGH GdLfhHi agh cQSe eG Ydi XgQ GdCSWQdGH GdTeGdi ShGA s
(3QHeG eCNhP ef cJGH LGeY GdeHGOF hGdZGjGJ ddeQGcTis
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B203 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B286s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3(3V(B1 - (3bSe (B1 - (3U (B27 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B572s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3ejbGJ (B115) s
Keywords: (3Gdadcs